Penguatan Profitabilitas dalam Meningkatkan Pengaruh Enterprise Risk Management pada Nilai Perusahaan Perbankan di Indonesia - Mauliddah, Nurullaili; Fatihudin, Didin; Oktaviani, Marista; Prasasti, Karari Budi (Universitas Muhammadiyah Palembang, 2025)
As a company tasked with catalyzing the economy, banking has a level of profitability and risk that needs to be considered. The dangers faced include a decrease in profitability and company value. This research aims to analyze the influence of profitability moderation on the influence of company size and Enterprise Risk Management (ERM) on banking company value. Using purposive sampling, this research found 11 samples of conventional banking companies listed on the IDX in 2018-2021 and analyzed using the Moderation Regression Analysis (MRA) method with SPSS 25. The results of the research show that without and with ROE as a moderating variable, the influence of company size on company value remains significant and increases when there is ROE as moderating variable; however, the ERM variable with or without ROE as a moderating variable still does not have a considerable influence on company value.